2001
DOI: 10.2516/ogst:2001006
|View full text |Cite
|
Sign up to set email alerts
|

The Shape and Stability of Small Liquid Drops on Fibers

Abstract: Résumé -Forme et stabilité de gouttelettes de liquide sur des fibres -La forme d'une petite goutte de liquide sur une fibre de petit diamètre peut être décrite soit par une allure en tonneau axé symétrique, soit par une allure en perle (cloche). Les expériences montrent que lorsque le volume réduit, défini par le rapport entre le volume de la goutte et le rayon de la fibre, est grand, la configuration préférée est celle en tonneau. Lorsque le volume réduit est petit, une transition se produit vers la forme en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 17 publications
2
94
0
1
Order By: Relevance
“…These results are compared to literature date on the roll-up transition and to theoretical predictions on the metastability of the axially symmetric barrel shape conformation [18]. A conjecture on the role of the inflection angle in the profile of the barrel drops is also considered [19]. The comparison shows that the absolute stability curve best corresponds to the experimental data.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…These results are compared to literature date on the roll-up transition and to theoretical predictions on the metastability of the axially symmetric barrel shape conformation [18]. A conjecture on the role of the inflection angle in the profile of the barrel drops is also considered [19]. The comparison shows that the absolute stability curve best corresponds to the experimental data.…”
Section: Introductionmentioning
confidence: 70%
“…According to Carroll's criterion points above this line correspond to stable barrel shaped droplets and points below this line correspond to metastable conformations possessing axial symmetry. McHale et al, re-examined this argument and demonstrated that the region above this curve can be further divided into two types as indicated by the dotted curve in figure 3 [19]. Above the dotted curve barrel shaped droplets with an inflection point in their profile occur, whereas below the dotted curve the barrel shaped droplets have no inflection in their profile.…”
Section: Stability Conditions and Comparison To Datamentioning
confidence: 99%
See 2 more Smart Citations
“…4.2, we do not consider the exact shape of the drop on the helical fiber. However, McHale et al [16] and Eral et al [17] have shown that on a straight fiber, a drop adopts either a barrel or a clamshell shape as a function of its volume, the contact angle and the radius of the fiber. In our situation, the transition between both configurations may impact the length of the contact line between the drop and the fiber and thus the capillary force.…”
Section: Drop Shapementioning
confidence: 99%